Pembandingan Kinerja Menggunakan Rasio Keuangan Pada Perusahaan Sektor Energi Yang Terdaftar DI BEI Periode 2019 – 2023 - Cholis Hidayati; Desinta Leba; Maria Dinda A; Allysia Safira P. P; Lisa Lavenia; Hanum Cheffi A (GLOBAL SCIENTS PUBLISHER, 2025)
This research aims to analyze and compare the financial performance of energy sector companies listed on the Indonesia Stock Exchange for the period 2019 to 2023. The research sample consists of five companies: ABMM, ADRO, CNKO, MEDC, and INDY. The analysis used is financial ratios such as the current ratio, short-term ratio, average age of receivables, inventory turnover ratio, fixed asset turnover ratio, total asset turnover ratio, total debt to total assets, time interest rate, fixed cost coverage, and profit. margins. This will do. ROA, ROE, PER, dividend yield, dividends. These companies faced complex challenges and dynamics during the study period, including the COVID-19 pandemic and energy transition trends. This research provides insight into the financial health of energy sector companies in Indonesia. Overall, the majority of companies show a trend of improving performance in 2023, indicating good adaptation to market conditions and the effectiveness of operational strategies implemented.